Marketing. What is market segmentation. - Business Professor ([Place of publication not identified] : Business Professor, 2021)
This video explains Marketing - What is Market Segmentation.
Title from resource description page (viewed March 7, 2022).
In English.
Keywords: Market segmentation; Marketing -- Management; Consumers -- Research; Consumers' preferences; Segmentation du marché.; Marketing -- Gestion; Consommateurs -- Recherche; Consommateurs -- Préférences.; Consumers' preferences; Consumers -- Research; Market segmentation; Marketing -- Management; Educational films; Short films; Educational films; Short films; Films éducatifs.; Courts métrages.